DETERMINAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH BANK SYARIAH INDONESIA DENGAN MODEL CARTER - Trisasmita, Rio; Supriyadi, Lili (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
This study aims to collect empirical evidence regarding the effect of the CARTER variable partially and simultaneously on customer satisfaction at Bank Syariah Indonesia. The method used in this research is Multiple Linear Regression Analysis. The results obtained indicate that the service quality of compliance, assurance, reliability, tangible, empathy, and responsiveness partially has a significant effect on customer satisfaction. Service quality compliance, assurance, reliability, tangible, empathy, and responsiveness together have an effect on customer satisfaction. The implication of this research is that it focuses on compliance, assurance, reliability, tangible, empathy, and responsiveness which can affect customer satisfaction at Bank Syariah Indonesia. The results of this study have previously had similarities and differences with previous studies. The similarity is that both use the CARTER dimension and the difference with previous studies using service quality measurements with the Servqual dimension.